Cara hidup Islam di kalangan masyarakat Langkawi: Suatu kajian di Mukim Kuah, Langkawi Kedah / Md. Saufi Abdul Hamid - Md. Saufi , Abdul Hamid (2005)
Islamic Lifestyle in the Islamic Society in Langkawi Island: A Study in the district of Kuah. bissertation, Kuala Lumpur: Academy of Islamic Studies, University of Malaya, 2005 This dissertation scrutinizes the detail of lifestyle of the Muslim society in the district of Kuah in Langkawi Island which is well known as Tourism City. It is pertinent to explain and elaborate whether or not the tourism industry has influenced the Islamic lifestyle of the local people in Langkawi. The importance of this study is to find a significant connection between the progress or development of tourism industry and the lifestyle of the Muslim in Langkawi. This research is specifically conducted to find solutions for the following problems; What is the level of obedience towards the tenets of Islam among the Muslim Society in Kuah? What is the trend of their clothing in this district? How is the Muslim daily social pattern in Kuah? In order to find the answers to the above question, the writer had randomly selected four hundred respondents from the Muslim society in Kuah. Other methods such as historic, documentation, interview, questionnaire and observation are also used as a mean to obtain adequate information for this research. As a conclusion, the findings of this research are; The level of obedience towards the tenets of Islam among Muslim Society in Kuah is unsatisfactory especially in term of prayer. The same could be said to the way the women dress and cover themselves. However, the socializing trend in this society is in accordance to Islamic lifestyle. All the finding from the research are presented in detail in chapter IV.